Telomere shortening in mucosa surrounding the tumor: Biosensor of field cancerization and prognostic marker of mucosal failure in head and neck squamous cell carcinoma. Issue 5 (May 2015) - Boscolo-Rizzo, Paolo; Rampazzo, Enrica; Perissinotto, Egle; Piano, Maria Assunta; Giunco, Silvia; Baboci, Lorena; Spinato, Giacomo; Spinato, Roberto; Tirelli, Giancarlo; Da Mosto, Maria Cristina; Del Mistro, Annarosa; De Rossi, Anita
Abstract : Highlights: Evaluation of telomere length and levels of TERT in cancer tissues and tumor surrounding mucosa (SM). No correlation was found between age and telomere length in SM. Patients with short telomeres in SM had a significantly higher risk of mucosal failure. Patients with high TERT levels in cancer tissues had a significantly higher risk of regional failure. Telomere erosion is a biosensor of field cancerization and precedes the reactivation of TERT in SM. Summary: Objectives: The aim of the present study was to investigate the pattern of telomere length and telomerase expression in cancer tissues and the surrounding mucosa (SM), as markers of field cancerization and clinical outcome in patients successfully treated for with head and neck squamous cell carcinoma (HNSCC). Materials and methods: This investigation was a prospective cohort study. Telomere length and levels of telomerase reverse transcriptase (TERT) transcripts were quantified by real-time PCR in cancer tissues and SM from 139 and 90 patients with HNSCC, respectively. Results: No correlation was found between age and telomere length in SM. Patients with short telomeres in SM had a higher risk of mucosal failure (adjusted HR = 4.29). Patients with high TERT levels in cancer tissues had a higher risk of regional failure (HR = 2.88), distant failure (HR = 7.27), worse disease-specific survival (HR for related death = 2.62) but not mucosal failure. High-risk patients having both short telomeres in SM and high levels of TERT in cancer showed a significantly lower overall survival (HR = 2.46). Conclusions: Overall these findings suggest that telomere shortening in SM is a marker of field cancerization and may precede reactivation of TERT. Short telomeres in SM are strongly prognostic of mucosal failure, whereas TERT levels in cancer tissues increase with the aggressiveness of the disease and are prognostic of tumor spread.